30th annual gathering of the B.Y.P.G. youth group - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of attendees for the 30th annual gathering of the B.Y.P.C. (Baptist group), in front of the San Jose Civic Auditorium.